(untitled) (Third Sector Social Economic Review, 2022)
The present study aims not only to determine the impact of brand gender on brand usage intent and purchase intention, but also to investigate the influence of consumer gender characteristics on research model relationships. This empirical study was conducted with a proposed model. The model was tested with surveys applied to a sample of 460 online food and beverage shoppers in Istanbul, Turkey. Regression analyses were conducted to test the research hypotheses. The study findings elicited the impact of feminine brand gender characteristic on brand usage intent and purchase intention, and masculine brand gender characteristic on only brand usage intent. Furthermore, the present study deepened the understanding of the influence of consumer gender personality traits on study correlations in the form of feminine and masculine genders. As a result of these effects, men intend to use masculine brands more, women intend to use feminine brands more, men intend to buy only masculine brands and women intend to buy only feminine brands. The relevant study underlined the impact of brand gender characteristics on brand usage intent and purchase intention and the effects of consumer gender characteristics on model correlations.